(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In international practice, many scientific and practical studies are carried out to improve the mechanisms for organizing and conducting customs audits, develop international standards, further develop the customs audit process. The article analyzes the fact that the introduction of the mechanism of customs audit in order to further improve efficiency in the country’s customs system is an urgent issue today, international practices and norms in the field of by, as well as the reforms of Customs Administration carried out in Uzbekistan and the priorities in national regulatory documents.